Phenotypic, genotypic and proteomic typing of invasive Group B Streptococcus isolated from humans and tilapia (Oreochromis spp. PISCES) in Malaysia - Muthanna, Abdulrahman Mansoor Mohammed (2023)
Streptococcus agalactiae, also called Group B Streptococcus (GBS), is a major cause of several infectious diseases in humans and fish. However, the likelihood of GBS transmission between different host species leading to a potential zoonotic problem is less well studied. This study aims to determine the phenotype, antimicrobial susceptibility, serotype, virulence and pili gene profiles, sequence type (ST) and proteomic profiles of GBS isolated from humans and cultured fish (tilapia) in Malaysia for comparison between both hosts for understanding its zoonotic and virulence potential. Considering the sporadic pattern of invasive GBS cases, particularly in humans, a total of 227 invasive GBS isolated from humans (n = 113) and tilapia (n = 114) were subjected to phenotyping, serotyping, antimicrobial susceptibility testing and detection of GBS virulence and pilus genes to allow comparison between two origins. Multilocus sequence typing (MLST), phylogenetic analysis and proteomic analysis were also performed for selected GBS isolates. All GBS isolated from humans and fish showed grey to white colonies with β haemolysis on blood agar, pink colonies on CHROMAgar and GBS brilliance agar, a positive CAMP test, a catalase-negative, and a positive GBS latex agglutination test. The most common serotype among human GBS strains was V (23%), followed by Ia (19.5%), II (18.6%), VI (15.9%), III (10.6%), VII (4.4%), Ib and IV, (3.5% each) and IX (0.9%), while all the fish isolates have serotype III (100%). Human isolates had a higher frequency of resistance to erythromycin (15%), azithromycin (13.3%), clindamycin (8.8%), chloramphenicol (2.7%) and ofloxacin (0.9%). However, the tetracycline resistance rate was higher in fish (98.5%) than in human isolates (75.3%). In the evaluation of the virulence and pili gene profiles, there were significant differences between the human and fish isolates in the genes rib, scpB, lmb, bac, PI -2a and PI -2b, but there were similarities in the genes cfb, cylE, hylB, fbsA, fbsB, spb1, bca and PI -1. Nineteen different sequence types (ST) were found among human isolates, where ST1 was the most predominant; interestingly, three novel sequence types, ST1668, ST1669 and ST1670, were also found. In addition, an unusual finding of the fish-adapted serotype III/ST283 was found in human isolates. On the other hand, all the randomly selected 15 fish isolates were ST283. In the phylogenetic analysis, there is a genetic linkage between both human and fish isolates sharing a similar lineage of CC283 in clade I. A total of 1405 proteins were identified by LCMS/MS in five human GBS and three fish strains belonging to ST283, ST1668, ST1669 and ST1670. A total of 1162 proteins were identified in the core proteome (with 82.5% similarity), 140 proteins were present in the human isolates, and 107 proteins were identified in the fish isolates. Proteins involved in stress response and gene expression regulation, metabolism, transcription and pathogenicity were also detected, reflecting the adaptability of GBS strains. This study suggests that human and fish GBS have similar phenotypic characteristics but differ in terms of virulence and pili gene profiles, antimicrobial susceptibility, serotype and sequence type. In addition, the proteomes of human and fish GBS isolates were found to be highly similar in this study.